Swertia kashmirensis, a new species from Bangus Valley of Kashmir Himalaya, India - Wani, Bilal A.; Islam, Tajamul; Khuroo, Anzar Ahmad; Ganie, Aijaz H.; Nawchoo, Irshad A. (Phytotaxa, 2022)
Swertia kashmirensis (Gentianaceae), a new species from Bangus Valley of Kashmir Himalaya, India is described here. The species resembles morphologically to Swertia thomsonii but differs markedly from it by cauline leaves free at base, petals having obtuse apices, nectaries oblong-oval, fimbriae 3–5, restricted on lower part of the nectary towards base of the petal, anthers obovate and dorsifixed.